1983
DOI: 10.1007/bf00264875
|View full text |Cite
|
Sign up to set email alerts
|

The use of irradiated pollen for differential gene transfer in wheat (Triticum aestivum)

Abstract: The use of irradiated pollen to bring about limited gene transfer in wheat has been investigated. Doses of X-rays of 2Kr, 3Kr and 5Kr were used to generate M1 progeny between maternal and paternal genotypes differing in quantitative and major gene characters. Cytological studies of M1 plants revealed hybrids with widespread aneuploidy and structural rearrangements in the paternal genome. These effects resulted in phenotypic variation between M1 progeny and complex multivalent formation at meiosis. All M1 plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

1984
1984
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 14 publications
1
18
0
1
Order By: Relevance
“…Experiments in barley, Hordeum vulgare (Powell et a!., 1983), wheat, Triticum aestivum (Snape et aL, 1983) and Indian mustard, Brassica juncea (Banga et a!., 1984), gave similar results to those with N. rustica and Z mays. There was maternalisation of Ml and M2 progenies, which increased with dose.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…Experiments in barley, Hordeum vulgare (Powell et a!., 1983), wheat, Triticum aestivum (Snape et aL, 1983) and Indian mustard, Brassica juncea (Banga et a!., 1984), gave similar results to those with N. rustica and Z mays. There was maternalisation of Ml and M2 progenies, which increased with dose.…”
Section: Introductionsupporting
confidence: 56%
“…The concept that the radiation-damaged segment of the paternal genome (deletions, mutations and chromosome rearrangements) which would survive and be expressed in the Ml but would normally be eliminated at the Ml meiosis and thus might account for high maternalisation of M2, as compared to unirradiated F2, (Zamir, 1983;Snape et a!., 1983;) also appears to be untenable for, in general, most observations have shown that the extent of variation in the Ml and M2 is in fact related. Significantly, it does not account for the maternalisation of Ml plants themselves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Il a souvent été constaté que la dose d'irradiation appliquée au pollen joue un rôle essentiel dans l'efficacité de la technique. Ainsi, généralement, des hybrides de phénotypes souvent anormaux et stériles (Powell et al, 1983;Daskalov, 1984; Engvild, 1985;Sari Gorla et al, 1987), résultant vraisemblablement d'un état d'aneuploïdie de leur contenu chromosomique nucléaire (Snape et al, 1983), sont obtenus à faibles doses. Lorsque la dose d'irradiation augmente, ces hybrides disparaissent progressivement au profit des haploïdes (Pandey et Phung, 1982;Raquin, 1985;Zhang et Lespinasse, 1991).…”
Section: Introductionunclassified
“…Experiments with several different plant genera have demonstrated that irradiation of pollen prior to fertilisation gives plants (M1 generation) whose progenies (M2) differ from normal crosses (F2) by expressing only a portion of the paternal genome (e.g., Pandey, 1975 and1980;Caligari, Ingram and Jinks, 1981;Powell, Caligari and Hayter, 1983;Snape, et a!., 1983 andDaskalov, 1984). Various mechanisms have been proposed to explain the observed results and these are discussed by Caligari, Powell and Hayter, 1984.…”
Section: Introductionmentioning
confidence: 99%